THE ONLINE COMMUNITY AS A MODERN MARKETING TOOL - Valeriia A. Demirova (Наука Красноярья)
Background. Today, a growing number of companies recognize the importance of forming and nurturing a community, making communities an essential marketing tool. These communities bring together like-minded individuals around a brand, enabling participants with shared interests, goals, or visions of the situation to interact, share experiences, and receive support.